Translation of the Holy Quran and the Role of Orientalist (IIUC Studies, 2009)
The full text of this article is in Arabic - see PDF below.doi: 10.3329/iiucs.v4i0.2862 IIUC STUDIES Vol. - 4, December 2007 (p 57-74)